The impact of night shift work on health and social life among technical employees in Global Rail Malaysia Sdn Bhd and Rapid Rail Sdn Bhd in MRT Kajang line - Badrul Hisham Bahari, (Open University Malaysia, 2021)
Shift work is considered necessary especially to industries that provides 24/7 services to the community. In particular, night shift can have negative impact on health and well-being of the employees as it can cause disturbance of the normal circadian rhythms, causing significant alterations of sleep and biological functions including disturbances to eating habits, which in long run can increase the risk of hypertension, diabetes and obesity. Employees working on night shift have more difficulties to lead a healthy social life with many of them found difficult to be there for their families especially when it comes to social gatherings among family members. After some time, this will affect the marital relationship, care of children and social contacts. The aim of this paper is to analyse whether the night shift work has any impact on the health and social life of technical employees in Global Rail Sdn Bhd and Rapid Rail Sdn Bhd in MRT Kajang Line. To analyse the data in this study, SPSS Statistics 21 was used. The findings conclude that night shift has significant influence to sleep deprivation and obesity among the respondents. This study could help the MRT or rail industry in designing policies and creating cultures that could encourage their employees to lead a better healthy lifestyle and health regime so that the night shift does not lead to negative impact to the employees’ health and social life. (Abstract by author)